Identification of AMOTL2 as an antiviral factor that enhances the human type I interferon response against Zika virus - Alexandra C. Willcox; Theodore A. Gobillot; Caroline Kikawa; Nell E. Baumgarten; Caitlin I. Stoddard; Kevin Sung; Tamanash Bhattacharya; Tiia S. Freeman; Joshua Marceau; Daryl Humes; Julie Overbaugh (Proceedings of the National Academy of Sciences, 2025)
Zika virus (ZIKV) has caused multiple human outbreaks, with more recent epidemics associated with severe outcomes in infants. Today, ZIKV is endemic to many countries and presents a persistent threat for future epidemics. The host innate immune proteins that regulate ZIKV replication are incompletely defined. We developed a CRISPR knockout screen to identify host factors that impact ZIKV replication, resulting in the finding of angiomotin-like protein 2 (AMOTL2), a protein that inhibits ZIKV by regulating the host type I interferon (IFN) response. AMOTL2 affects IFN signaling by modulating STAT1 levels and activation in response to type I IFN. Thus, AMOTL2, which has largely been studied for its role in cancer, represents an antiviral protein that interacts with the IFN signaling pathway to promote downstream expression of IFN stimulated genes, resulting in restriction of ZIKV.